Pengaruh Perilaku Makan Ibu terhadap Perilaku Picky Eater Anak Usia Prasekolah - Budi Widyaningsih; Liftiah Liftiah; Widya Hary Cahyati (PAUDIA : Jurnal Penelitian dalam Bidang Pendidikan Anak Usia Dini, 2024)
Abstract One of the problems with the nutritional status of toddlers in Indonesia is the picky eater behavior of preschool children, during their growth and development period they require good nutrition. Picky eater behavior is a problem for mothers in accompanying their children's eating activities. This study aims to determine the influence of mothers' eating behavior on the picky eater behavior of preschool children. The research method used was quantitative research, the research location was a kindergarten in Candimulyo subdistrict, Magelang district, the number of respondents was 95 mothers. The measuring instruments used were CEBQ as a tool for measuring picky eater behavior and DEBQ as a tool for measuring maternal eating behavior. In this study, data were analyzed using bivariate tests with chi-square. The research results show that there is an influence of mother's eating behavior on picky eater behavior with a p value of 0.006. The conclusion is that mothers' eating behavior influences the picky eater behavior of preschool children. Mothers try to have good eating behavior to be a role model for their children by consuming healthy food. Key words: Picky eater behavior; maternal eating behavior; preschool age children Abstrak Salah satu permasalahan status gizi balita di Indonesia adalah perilaku picky eater anak usia prasekolah, di masa pertumbuhan dan perkembangannya membutuhkan pemenuhan gizi yang baik. Perilaku picky eater menjadi permasalahan ibu dalam mendampingi aktivitas makan anak. Penelitian ini bertujuan untuk mengetahui pengaruh perilaku makan ibu terhadap perilaku picky eater anak usia prasekolah. Metode penelitian yang digunakan dengan penelitian kuantitatif, lokasi penelitian di TK di kecamatan Candimulyo kabupaten Magelang, jumlah responden 95 ibu. Alat ukur yang digunakan menggunakan CEBQ sebagai alat ukur perilaku picky eater dan DEBQ sebagai alat ukur perilaku makan ibu. Dalam penelitian ini data dianalisis dengan uji bivariat dengan chi-square. Hasil penelitian menunjukan ada pengaruh perilaku makan ibu  terhadap perilaku picky eater dengan p value 0,006. Kesimpulannya adalah perilaku makan ibu mempengaruhi perilaku picky eater anak usia prasekolah. Ibu berupaya untuk memiliki perilaku makan yang baik agar jadi teladan bagi anaknya dengan mengkonsumsi makanan yang sehat. Kata kunci: Perilaku picky eater; perilaku makan ibu; anak usia prasekolah.